ANALISA TINGKAT PELAYANAN CHECK-IN DI TERMINAL KEBERANGKATAN DOMESTIK BANDAR UDARA ADISUTJIPTO YOGYAKARTA TERHADAP KEPUASAN PENUMPANG - Hary Soegiri; Kunthari Adzani Putri; Rachmadita Firdauzy Asj’ari (Approach : Jurnal Teknologi Penerbangan, 2019)
The aviation services industry in Indonesia has experienced very rapid growth. The more competition in the aviation industry, the more choices of goods or services offered, one of which is to offer the concept of "Low Cost Carrier". Yogyakarta Adisutjipto Airport is a fairly high airport level of service to the flow of passengers and goods. Every year the flow of passengers and goods is increasing but it is not proportional to the number of existing Check-in Counter. It is necessary to calculate the number of Check-in Counters needed to avoid long queues of passengers at check-in so that passengers are satisfied with the service. The research methodology uses quantitative research methods which is a process of finding knowledge that uses data in the form of numbers as a means of analyzing information about what you want to know. Data obtained from direct observation, surveys, questionnaires and literature studies. For the method of analysis using the help of SPSS applications in which there are validity tests, reliability tests, regression tests. The results of this study are that passengers are not satisfied with check-in services at the Domestic Departure Terminal of Adisutjipto International Airport, Yogyakarta because the area of check-in area and the number of check-in counters available cannot serve passengers optimally. The performance of the check-in counter service is not in accordance with the standard that is 0.5 in the category "D" where the level of service and comfort is sufficient, the movement / flow is not stable, delays can be accepted.